تأثير الوسط المغذّي وPHوالجهات الأربع للأشجار ومدّة حفظ الأوراق المصابة في إنبات الأبواغ الكونيدية للفطر Spilocaea oleagina المسبب لمرض عين الطاووس في محافظة طرطوس - حسن, محمود (Latakia University Journal -Biological Sciences Series, 2019)
أظهرت نتائج البحث أنّ حيوية الأبواغ الكونيدية تحت الظروف الحقلية كانت عالية في شهري نيسان وأيار، ومتوسطة في تشرين الأول وتشرين الثاني، ومنخفضة في بقية الأشهر. حفّزت العناصر الغذائية الأبواغ الكونيدية على الإنبات . نبتت الأبواغ الكونيدية في مجال واسع من درجات pH في (12-5) و كانت الدرجة المثلى للإنبات هي 10 pH. وجد اختلاف في نسبة إنبات الأبواغ الكونيدية المجموعة من الجوانب المختلفة للأشجار و كان الإنبات أكبر في الجانب الشمالي وأقّّل نسبياً في الجوانب المتبقّية.و تناسبت حيوية الأبواغ الكونيدية تناسباً عكسياًً مع مّدة حفظها. The results of this research show that the viability of conidiospores under field conditions is high during April and May, moderate during October-November, compared to the rest of year. Nutrients have stimulated the conidiospores to germinate. Conidiospores has germinated at a wide range of pH (12-5), with optimum germination at pH 5-12. According to the various tree sides, differences in the rate of conidiospores germinations have been noticed, where the highest germination rates are in the north side of the trees, compared with germination rates in other sides. The viability of conidiospores has decreased during the conservation period.